Effect of jump exercise training on long‐term head‐down bed rest‐induced cerebral blood flow responses in arteries and veins. Issue 7 (3rd May 2021) - Ogoh, Shigehiko; Sato, Kohei; de Abreu, Steven; Denise, Pierre; Normand, Hervé
Abstract : New Findings: What is the central question of this study? What is the effect of an exercise countermeasure on microgravity‐induced change in cerebral blood flow? What is the main finding and its importance? Jump exercise training as a countermeasure did not modify the heterogeneous cerebral blood flow response to head‐down bed rest, suggesting that this method is effective in preventing cardiovascular system deconditioning but is not good for cerebral haemodynamics. Abstract: This study aimed to examine the effect of an exercise countermeasure on cerebral blood flow (CBF) response to long‐term −6° head‐down bed rest (HDBR) in all cerebral arteries and veins. Twenty male volunteers were exposed to HDBR for 60 days with (training group, n = 10) or without (control group, n = 10) jump exercise training as a countermeasure to spaceflight. The blood flow in the neck conduit arteries (internal carotid and vertebral artery; ICA and VA) and veins (internal jugular and vertebral veins; IJV and VV) was measured, using ultrasonography before (baseline) HDBR, on the 30th and 57th day of HDBR. Long‐term HDBR causes a heterogeneous CBF response between the anterior and the posterior brain or between arteries and veins. Long‐term HDBR decreased anterior cerebral arterial and venous blood flow, while posterior cerebral arterial and venous blood flows were well maintained. However, exercise jump training did not change each arterial and venous CBF responses to HDBR (control vs. training; ICA, P = 0.643; VA, P = 0.542; external carotid artery, P = 0.644; IJV, P = 0.980; VV, P = 0.999). These findings suggest that jump exercise training did not modify the heterogeneous CBF response to long‐term HDBR. Abstract :